Risk tolerance and entrepreneurship - Hans K. Hvide; Georgios A. Panos (Institute for the Study of Labor (IZA), 2013)
A tradition from Knight (1921) argues that more risk tolerant individuals are more likely to become entrepreneurs, but perform worse. We test these predictions with two risk tolerance proxies: stock market participation and personal leverage. Using investment data for 400,000 individuals, we find that common stock investors are around 50 percent more likely to subsequently start up a firm. Firms started up by stock market investors have about 25 percent lower sales and 15 percent lower return on assets. The results are similar using personal leverage as risk tolerance proxy. We consider alternative explanations including unobserved wealth and behavioral effects.
Keywords: L26; 330; entrepreneurial entry; entrepreneurial performance; firm entry; firm performance; firm productivity; firm survival; overconfidence; risk aversion; risk tolerance; stock market participation